Keluarga Sebagai Wadah Pola Pendidikan Karakter: Optimalisasi Peran Orangtua Sebagai Pendidik Pendidikan Karakter Bagi Remaja Usia 13-17 Tahun di Lembang Makkodo Kecamatan Simbuang - Bartolomius Budi; Salmon Andi Padang; Mersi Pondi; Marthinus Kabe; Ronaldo Stefanus (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This research discusses about optimizing the role of parents as educators of character education in the family for teenagers aged 13-17 years old in Lembang Makkodo, Simbuang District. Character education in the family is very important considering the increasingly strong influence of the environment and information and communication technology on the lives of teenagers today. This research uses descriptive qualitative methods and data collection techniques through interviews with parents and teenagers aged 13-17 years old. The results obtained in this research are that parents have made the family a place for character education for children, especially teenagers, so that teenagers know and have good character. The pattern of character education carried out by parents is through teaching at the dinner table and at every opportunity at home, such as storytelling and discussion. The parents have an optimal role in educating teenagers about good character, but some teenagers are still influenced by the environment and technology so that some forget what their parents taught for them. Therefore, synergy between family, school, and community is needed to strengthen character education for teenagers.